Strategic Orientation of Malaysian Mobile Communication Service Providers [A Study On Managerial Perspectives] - S Kolondasamy, John Micheal (2010)
The aim of this paper is to investigate the strategic orientation of Malaysian mobile communication service providers through the perspectives of managers in the industry. Focus is to understand extent of strategic orientation of the players and validate strategic orientation and business performance relationship in the sector.The study contributes to the body of literature through an examination of trends and development in strategic orientation, market dynamics and business performance topics. Focus was on studies specifically related to relationship between strategic orientation and business performance in given market dynamics or condition. Data was collected from two (2) of the leading mobile communication service providers in Malaysia using administered questionnaire. Then after, data was analyzed using statistical analysis software.Results of the empirical investigation indicate manager’s strong agreement to supply and competition to be influential market forces in Malaysian mobile communication service sector. Investigation on the extent of strategic orientation have resulted competitor orientation to have higher perception among strategic orientation components by managers within the sector. Observed positive relationship between strategic orientation and business performance and most appealing orientation is interfunctional coordination with significant correlation to most number of business performance measures i.e. Service Quality, Customer Satisfaction and Profit Margin Growth. The paper concludes with a summary of research findings in relation to research objectives, implications of the study on theoretical and managerial perspectives and thoughts on study limitation and ideas for future research.